2004
DOI: 10.1079/phn2003527
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, familial and trait predictors of fruit and vegetable consumption by pre-school children

Abstract: Objective: To examine the contribution to fruit and vegetable eating in children of potential predictive variables within the domains of demographics, parental feeding practices and personality traits. Design: Cross-sectional survey. Setting: Questionnaires were distributed to parents through 22 London nursery schools. Subjects: Questionnaires were completed and returned by 564 parents or principal caregivers of 2-6-year-old children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

43
389
8
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(463 citation statements)
references
References 41 publications
43
389
8
23
Order By: Relevance
“…Patterns of family meals, especially meals eaten together, positively affect the consumption of F&V (4,7,9,30) . Children like to consume products they know -the more often children eat a given product, the more they like it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patterns of family meals, especially meals eaten together, positively affect the consumption of F&V (4,7,9,30) . Children like to consume products they know -the more often children eat a given product, the more they like it.…”
Section: Discussionmentioning
confidence: 99%
“…Children like to consume products they know -the more often children eat a given product, the more they like it. Children familiarize themselves with new tastes and products through experience as well as by observing dietary behaviours of other people present in their environment (parents, siblings, peers) (4,31,34,35) . The present study confirmed the role of the influence exerted by the family environment and health-oriented attitudes of parents (parents eating F&V, encouraging children to eat F&V, giving sliced F&V between meals, giving children F&V to take to school) on the F&V consumption of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of epidemiological studies have been published showing the association of infant feeding practices with later intake of fruit and vegetables (13)(14)(15)(16)(17) . To our knowledge, however, this association has not previously been described in non-Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Children in high SES families, for example, drink fewer soft drinks and consume more fruits, vegetables, high-fibre bread, cereals, vitamins and foods low in monounsaturated fats than children in low SES homes 9,10 . In addition, children of mothers with more education eat more vegetables 11 , and parents' higher education is associated with a more desirable level of nutrient and vitamin intake in children 12 .…”
mentioning
confidence: 99%